Impact of Ship Motions on Maritime Radio Links - William Hubert; Yvon-Marie Le Roux; Michel Ney; Anne Flamand (International Journal of Antennas and Propagation)
The improvement of maritime radio links often requires an increase of emitted power or receiver sensitivity. Another way is to replace the poor antenna gains of traditional surface ship whips by novel antenna structures with directive properties. However, ship motions, especially when launches are involved, may affect the radio link quality. Therefore, a tool for modelling the impact of ship motions on such antenna structures was developed. It helps the specification of antenna radiating parameters and improves the radio link performance evaluation. This tool includes a deterministic two-ray model for radio-wave propagation over the sea surface. The geometrical 3D engine for ship motions has the advantage to be compatible with any propagation model and antenna structure.